Characterization of self-assembled polyelectrolyte complex nanoparticles formed from chitosan and pectin - Birch, Nathan P (Langmuir : the ACS journal of surfaces and colloids, 2014)
Chronic wounds continue to be a global healthcare concern. Thus, the development of new nanoparticle-based therapies that treat multiple symptoms of these "non-healing" wounds without encouraging antibiotic resistance is imperative. One potential solution is to use chitosan, a naturally antimicrobial polycation, which can spontaneously form polyelectrolyte complexes when mixed with a polyanion in appropriate aqueous conditions. The requirement of at least two different polymers opens up the opportunity for us to form chitosan complexes with an additional functional polyanion. In this study, chitosan:pectin (CS:Pec) nanoparticles were synthesized using an aqueous spontaneous ionic gelation method. Systematically, a number of parameters, polymer concentration, addition order, mass ratio, and solution pH, were explored and their effect on nanoparticle formation was determined. The size and surface charge of the particles were characterized, as well as their morphology using transmission electron microscopy. The effect of polymer concentration and addition order on the nanoparticles was found to be similar to that of other chitosan:polyanion complexes. The mass ratio was tuned to create nanoparticles with a chitosan shell and a controllable positive zeta potential. The particles were stable in a pH range from 3.5 to 6.0 and lost stability after 14 days of storage in aqueous media. Due to the high positive surface charge of the particles, the innate properties of the polysaccharides used, and the harmless disassociation of the polyelectrolytes, we suggest that the development of these CS:Pec nanoparticles offers great promise as a chronic wound healing platform